Effect of Hexadecyltrimethyl-Ammonium Loaded Montmorillonite on The Cu Adsorption: Adsorption Surface Sites Involved - Fernández Morantes, César (2019)
Na raw montmorillonite (Mt) and two organomontmorillonites (OMt) with different hexadecyltrimethylammonium bromide (HDTMABr) was used to adsorb Cu2+. TheCu2+ adsorption isotherms were performed, and Langmuir, Freundlich and SIPS mathematical models were evaluated.According to the R2 term, the experimental data were appropriately described by SIPS models for all the samples.Thermal analysis of the OMt adsorbents and their Cu2+ adsorbed products indicated that HDTMA was associated with cation exchange and Van der Waals interactions to the Mt surface. The decrease of the de-surfactant temperaturemainly for MH0.5-Cu respect to MH0.5 sample would indicate a weaker Van der Waals interactions of alkyl chains at the external surface by the Cu presence. The Cu2+ and the HDTMA entrance at the interlayer of Mt was evidenced by XRDanalysis, where the cationic exchange process occurs. The zeta potential values behavior evidenced the importance of the external surface participation in the Cu2+ adsorption mainly for OMt samples.